Amino Acids That Centrally Influence Blood Pressure and Regional Blood Flow in Conscious Rats. (29th May 2012) - Takemoto, Yumi
Abstract : Functional roles of amino acids have increasingly become the focus of research. This paper summarizes amino acids that influence cardiovascular system via the brain of conscious rats. This paper firstly describes why amino acids are selected and outlines how the brain regulates blood pressure and regional blood flow. This section includes a concise history of amino acid neurotransmitters in cardiovascular research and summarizes brain areas where chemical stimulations produce blood pressure changes mainly in anesthetized animals. This is followed by comments about findings regarding several newly examined amino acids with intracisternal stimulation in conscious rats that produce changes in blood pressure. The same pressor or depressor response to central amino acid stimulations can be produced by distinct mechanisms at central and peripheral levels, which will be briefly explained. Thereafter, cardiovascular actions of some of amino acids at the mechanism level will be discussed based upon findings of pharmacological and regional blood flow measurements. Several examined amino acids in addition to the established neurotransmitter amino acids appear to differentially activate brain structures to produce changes in blood pressure and regional blood flows. They may have physiological roles in the healthy brain, but pathological roles in the brain with cerebral vascular diseases such as stroke where the blood-brain barrier is broken.